Kecerdasan Buatan: Plagiarisme dan Perilaku Mandiri Siswa Sekolah Menengah Atas Dalam Penggunaan ChatGPT - Budi Susilo; Tri Widayanti (STIKes Ibnu Sina Ajibarang, 2024)
The use of artificial intelligence has significantly transformed learning methods and processes. Previous research indicates that artificial intelligence can enhance independent learning behavior but also has the potential to increase plagiarism issues. This study aims to statistically examine the relationship between the use of artificial intelligence and plagiarism, as well as independent learning behavior. The research adopts a descriptive associative quantitative approach through surveys conducted at several high schools in Pontianak. The study population comprises students who are familiar with the ChatGPT application. The variables are the use of ChatGPT, plagiarism, and independent learning behavior. Data were collected through questionnaires from 50 respondents and analyzed using descriptive and inferential statistics. This study examines the analysis results using SPSS. Descriptive analysis shows that 56% of respondents are male and 44% are female. The results indicate that 68.8% of males are involved in plagiarism, and 55.6% exhibit independent learning behavior. Inferential analysis shows no significant relationship between the use of ChatGPT and plagiarism or independent learning behavior, based on the very low and insignificant values of Phi, Cramer's V, and Contingency Coefficient (p-value > 0.05).